Studying a bachelor's degree as motivation to reduce vulnerability and discrimination against indigenous women in Mexico. Experiences from the voices of UIET graduates - Negrín Nieto, Gerson; Pérez Vargas, Adriana; Galindo Quintanilla, Tania Leslie (Emerging Trends in Education, 2026)
This research sought to determine the impact that higher education offers on the empowerment of indigenous migrant women educated at the Intercultural University of the State of Tabasco (UIET). The project is a descriptive qualitative project that used interviews as a data-gathering technique to address the cases of ten indigenous women who studied at the institution and who, to access this opportunity, had to migrate temporarily or permanently from their hometowns. The study explored their adaptation process, as well as the resulting changes in their ways of thinking and perceiving realities, their identities, and representations of empowerment from the moment they had to leave home and their communities until they completed a bachelor's degree and began working or enrolled in a master's degree. The participants' main motivation for attending university was to contribute to the eradication of discrimination, followed by a career in which they could generate new knowledge and share it with others. The fact that the university offered innovative programs focused on vulnerable populations, such as rural and indigenous communities, also motivated them to study
Keywords: social inequality; empowerment; gender studies; university; vulnerability